Membangun Perspektif Baru Administrasi Publik : Teori, Konsep, dan Implikasinya dalam Kepemimpinan Desa - Yosi Muhaemin (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
This study examines the development of public administration theories and concepts, emphasizing their relevance to village leadership and development planning. Public administration as a discipline has undergone significant paradigm evolution, from Old Public Administration (OPA) emphasizing hierarchical bureaucracy, New Public Administration (NPA) emphasizing social justice, New Public Management (NPM) emphasizing managerial efficiency and effectiveness, to New Public Service (NPS) emphasizing democratization, participation, and community-based public services. This paradigm shift demonstrates a transition from a rigid governance model to an adaptive, inclusive, and accountable public service model. In the context of village development, competency theory and public leadership play a crucial role because the village head is the primary actor in ensuring development direction aligned with community aspirations. The village head functions not only as an administrative leader but also as a driver of citizen participation, a facilitator of sustainable development, and a guarantor of public accountability. Therefore, the village head's competencies, including knowledge, skills, and leadership attitudes, must be systematically developed to address local development challenges. This study integrates administrative theory, public administration paradigms, competency theory, and village development planning concepts to offer a new perspective on locally-based public administration. The study's findings indicate that adaptive public administration must strategically position village leadership, strengthen individual and institutional capacity, and internalize the principles of good governance in development implementation.